Поетика «Євангельского» циклу Л. Андрєєва - Залозна, Ксенія Андріївна; Zalozna, Ksenia A. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Об'єкт аналізу - твори, що склали «євангельський» цикл Л. Андрєєва. Предмет дослідження – поетика кожного з творів, що входить у цикл, і циклоутворюючі фактори. Мета – усвідомити особливості поетики та авторської концепції Л. Андрєєва у «євангельському» циклі.

The object of analysis is the creation of the “evangelical” cycle of L. Andreev. The subject of research is the poetics of skin products that enter the cycle and cycle-stimulating factors. Meta - to become aware of the peculiarities of poetics and the author’s concept of L. Andreev in the “evangelical” cycle.
Poetics of the “Gospel” cycle by L. Andreev
Keywords: Історія та актуальні проблеми вивчення «Євангельського» циклу Леоніда Андрєєва; Особливості поетики «Юди Іскаріота» та «Бен-Товита»; Поетика оповідання «Елеазар»; History and current problems of studying the "Gospel" cycle of Leonid Andreev; Features of the poetics of "Judas Iscariot" and "Ben-Tobit"; Poetics of the story "Eleazar"